Early Intelligence Detection of LGBT in the Selection of Indonesian National Police (POLRI) Recruits - Trapsilo, Firso (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This study focuses on early detection of the threat of LGBT inclusion in the Indonesian National Police, primarily by selecting police recruits. This research uses a qualitative method with a descriptive design. The results of the study show that there is evidence of LGBT threats to the Police, both at the recruitment selection stage as well as among active members of the Police. Early detection and prevention efforts against this threat need to focus on strengthening the criteria and stages of the selection of police recruits. Especially at the Mental and Personality Investigation (in Bahasa Indonesia: Penelusuan Mental Kepribadian or Mental and Personality Investigation) stage. This research then suggests a procedure for checking social media as one of the stages in the selection of police officers and the need for more detailed indicators as guidelines for assessing LGBT threats at the selection stage of police officers.